Colourful Healthy Cole Vegetables Sneaking in Indian Kitchens - Singh, Shrawan; Kalia, Pritam (Indian Horticulture, 2025)
Colourful cole vegetables, including cabbage, cauliflower, broccoli, Brussels sprouts, kohlrabi, and kale, are gaining popularity in India for their aesthetic appeal and significant health benefits. Traditionally, Indian consumers have preferred white cauliflower and green broccoli, but recent trends show growing interest in biofortified coloured variants such as red cabbage, orange and purple cauliflower, and various coloured broccoli types. These vibrant vegetables are rich in health-promoting compounds like glucosinolates, anthocyanins, β-carotene, and chlorophyll, which contribute to disease prevention and overall wellness. Natural mutations, such as the Or and Pr genes, have enabled the development of these colourful varieties without involving GMOs, making them consumer friendly. Their visual appeal enhances garden aesthetics and encourages healthy eating, especially among children. Furthermore, these vegetables are ideal for microgreens, providing dense nutritional content and culinary versatility. This rising consumer acceptance highlights the potential of colourful cole vegetables in promoting nutrition-sensitive agriculture in India.